Pencegahan Breast Cancer dan Cervical Cancer dengan Penggunaan Pembalut Sehat - Nabila Nurhaliza; Dwiva Azmar Kurnia; Nursamsi Nursamsi; Enita Anggraeni (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Breast cancer (carcinoma mammae) is a type of cancer that can affect both women and men, especially women. This breast cancer grows in the glands, fatty tissue, or connective tissue of the breast. One way to prevent breast cancer is to do breast self-examination (BSE). This behavior can be done by all women. Cervical cancer is a malignant tumor in women that attacks the female reproductive organs, namely the vaginal mucosa and the area around the cervix, commonly known as the lower part between the female reproductive organs and the uterus. Cervical cancer is caused by the HPV virus. One way to prevent cervical cancer is to use healthy pads. Objective: This health education will provide education on prevention of breast cancer with BSE behavior and cervical cancer by using healthy sanitary napkins for female students of SMPN 1 Cikoneng so that they understand and understand how to prevent these two diseases. Method: Counseling was carried out at one of the schools in Ciamis Regency, namely SMP Negeri 1 Cikoneng which was the main target of this counseling. The partners in this health consultation were 61 female students at SMP Negeri 1 Cikoneng. The method used is a quantitative method, seminars and interviews that begin with conducting a survey to explore the level of knowledge of the students about the prevention of breast cancer and cervical cancer. Then, preparing material to be delivered in powerpoint form and preparing questionnaires to be worked on by the students. Result: The results of the counseling survey involved 61 participants using interviews in the pre-test and questionnaires in the post-test. The researcher analyzed the completed questionnaires to determine the level of knowledge of students about preventing breast cancer and cervical cancer by using sanitary pads before and after health education activities. Conclusion: Health education Increase awareness of adolescents to pay more attention to sanitary pads during menstruation to avoid cervical cancer and to always perform BSE behavior every month on the 7th-10th from the first day of menstruation so that they know signs of breast cancer.